2014
DOI: 10.1038/srep06272
|View full text |Cite
|
Sign up to set email alerts
|

Taichi-inspired rigid-flexible coupling cellulose-supported solid polymer electrolyte for high-performance lithium batteries

Abstract: Inspired by Taichi, we proposed rigid-flexible coupling concept and herein developed a highly promising solid polymer electrolyte comprised of poly (ethylene oxide), poly (cyano acrylate), lithium bis(oxalate)borate and robust cellulose nonwoven. Our investigation revealed that this new class solid polymer electrolyte possessed comprehensive properties in high mechanical integrity strength, sufficient ionic conductivity (3 × 10−4 S cm−1) at 60°C and improved dimensional thermostability (up to 160°C). In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 41 publications
(49 reference statements)
1
88
0
Order By: Relevance
“…15 The morphology, electrochemical window, and ionic conductivity of the obtained cellulose-supported PEO-LiDFOB electrolyte were characterized and displayed in Figure 4. The SEM images showed that the PEO-LiDFOB electrolyte had smooth surface and a thickness of about 30 μm.…”
Section: Resultsmentioning
confidence: 99%
“…15 The morphology, electrochemical window, and ionic conductivity of the obtained cellulose-supported PEO-LiDFOB electrolyte were characterized and displayed in Figure 4. The SEM images showed that the PEO-LiDFOB electrolyte had smooth surface and a thickness of about 30 μm.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it was reported that a cellulose nonwoven membrane supported PEO:PCA:LiBOB SPE displayed ionic conductivity of 1.3 Â 10 À5 S cm À1 at 20 C. 22 These publications demonstrate the possibility of using natural materials for the design and fabrication of SPEs.…”
mentioning
confidence: 89%
“…Therefore the free volume around the polymer chain causes to the increase of the conductivity. The amorphous nature also provides a bigger free volume in the polymer blend electrolyte system with increasing temperature [63][64][65]. The activation energy values of different polymer blend electrolytes were calculated from the slopes of linear fit of the Arrhenius plots of different polymer blend electrolytes and these are displayed in Table 3.…”
Section: Impedance Spectroscopy Studiesmentioning
confidence: 99%